Desiccation tolerance of yeheb (Cordeauxia edulis Hemsl.) seeds - Liew, Josefine (2008)
In this master's thesis, the desiccation tolerance of seeds from yeheb, Cordeauxia edulis Hemsley, a multipurpose, evergreen shrub, native to the semi-desert areas in the horn of Africa, is studied. Due to overexploitation and bad regeneration, yeheb is now threatened with extinction.